1999
DOI: 10.1074/jbc.274.35.25113
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte Nuclear Factor 3 Relieves Chromatin-mediated Repression of the α-Fetoprotein Gene

Abstract: The ␣-fetoprotein gene (AFP) is tightly regulated at the tissue-specific level, with expression confined to endoderm-derived cells. We have reconstituted AFP transcription on chromatin-assembled DNA templates in vitro. Our studies show that chromatin assembly is essential for hepatic-specific expression of the AFP gene. While nucleosome-free AFP DNA is robustly transcribed in vitro by both cervical (HeLa) and hepatocellular (HepG2) carcinoma extracts, the general transcription factors and transactivators prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 75 publications
0
51
0
Order By: Relevance
“…We noticed that FoxA1 was expressed in MCF7 (as well as in the other ER␣-positive breast cancer cell lines analyzed) and HepG2 but not in HeLa and MDA-MB-231 cells (Crowe et al 1999;Williamson et al 2005), paralleling the cellspecific functional activity of enh2. As such we tested the hypothesis that FoxA1 could be important in determining an active chromatin structure at enh2 by performing DNase I sensitivity assays with nuclei isolated from MCF7 cells transfected with si LUC or si FoxA1.…”
Section: Functional Competency Of Enh2 Is Defined By Foxa1 and Is Crumentioning
confidence: 92%
“…We noticed that FoxA1 was expressed in MCF7 (as well as in the other ER␣-positive breast cancer cell lines analyzed) and HepG2 but not in HeLa and MDA-MB-231 cells (Crowe et al 1999;Williamson et al 2005), paralleling the cellspecific functional activity of enh2. As such we tested the hypothesis that FoxA1 could be important in determining an active chromatin structure at enh2 by performing DNase I sensitivity assays with nuclei isolated from MCF7 cells transfected with si LUC or si FoxA1.…”
Section: Functional Competency Of Enh2 Is Defined By Foxa1 and Is Crumentioning
confidence: 92%
“…It has recently been demonstrated that HNF-3 is such a factor and that its interaction with nucleosomal DNA is more stable than with free DNA (Cirillo and Zaret 1999). Furthermore, in vitro transcription assays using chromatin-assembled templates have shown directly that HNF-3 can relieve chromatin-mediated repression of alpha-fetoprotein gene expression (Crowe et al, 1999). Once bound, HNF-3 has been found to direct nucleosome positioning within the context of the albumin enhancer (McPherson et al, 1993;Cirillo et al, 1998;Shim et al, 1998;Cirillo and Zaret 1999).…”
Section: Hnf-3 and The Competence Of Endoderm To Adopt A Hepatic Fatementioning
confidence: 99%
“…In Vitro Transcription-DNA templates were in vitro transcribed upon addition of a RNA polymerase II-containing nuclear HeLa extract at a final protein concentration of 0.5 g/ l and an NTP/salts/energygenerating mix to give final concentrations of 0.7 mM CTP, UTP, GTP, ATP, 5 mM MgCl 2 , 66 mM KCl, 5 mM creatine phosphate, 10 units/ml of creatine kinase, 2.5 mM dithiothreitol, 9.0% glycerol and 18 mM HEPES (pH7.9) as described previously (28). Unless otherwise noted, all in vitro transcription reactions were performed with 500 ng of template DNA.…”
Section: Methodsmentioning
confidence: 99%